Quality of Chicken Sausage Coated by Transglutaminase-Crosslinked Bovine Split Hide Gelatin and Soy Protein Isolate Edible Film During Chilled Storage - Dwi Wulandari; Yuny Erwanto; Yudi Pranoto; Rusman Rusman; Sugiyanto Sugiyanto (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2020)
This research aims to determine the physical properties and the bacterial counts of chicken sausages that were given an edible coating made from a combination of bovine split hide gelatin and soy protein isolate with the addition of the enzyme transglutaminase during chilled storage. The parameters observed included, pH, moisture, protein content, weight loss, tenderness, and the bacterial counts. Data were analyzed with a completely randomized design (CRD) factorial pattern 4 x 4 with three replications. The first factor was the level of edible coating 0%, 5%, 10%, and 15% Â w/vol. The s factor was the storage time at 10Â°C which was 0, 5, 10, and 15 d. The results showed the pH and moisture during storage decreased, while the protein content, weight loss, tenderness, and the bacterial count sausages increased. Increasing the level of edible coating to hold sausage weight loss, while the pH and bacterial count of chicken sausage decrease. Increase the level of edible coating adds to the water content, protein content, and sausage tenderness. The use of a combined edible coating of bovine split hide gelatin and soy protein isolate with the addition of the enzyme transglutaminase to 15% could maintain the quality of chicken sausage based on national standard during 15 dof chilled storage BSN-3820-2015.